How Vision Affects Kinematic Properties of Pantomimed Prehension Movements - Fukui, Takao; Inui, Toshio (Frontiers in Psychology, 2013)
When performing the reach-to-grasp movement, fingers open wider than the size of a target object and then stop opening. The recorded peak grip aperture (PGA) is significantly larger when this action is performed without vision during the movement than with vision, presumably due to an error margin that is retained in order to avoid collision with the object. People can also pretend this action based on an internal target representation (i.e., pantomimed prehension), and previous studies have shown that kinematic differences exist between natural and pantomimed prehension. These differences are regarded as a reflection of variations in information processing in the brain through the dorsal and ventral streams. Pantomimed action is thought to be mediated by the ventral stream. This implies that visual information during the movement, which is essential to the dorsal stream, has little effect on the kinematic properties of pantomimed prehension. We investigated whether an online view of the external world affects pantomimed grasping, and more specifically, whether the dorsal stream is involved in its execution. Participants gazed at a target object and were then subjected to a 3-s visual occlusion, during which time the experimenter removed the object. The participants were then required to pretend to make a reach-to-grasp action toward the location where the object had been presented. Two visual conditions (full vision and no vision) were imposed during the pantomimed action by manipulating shutter goggles. The PGA showed significant differences between the two visual conditions, whereas no significant difference was noted for terminal grip aperture, which was recorded at the movement end. This suggests the involvement of the dorsal stream in pantomimed action and implies that pantomimed prehension is a good probe for revealing the mechanism of interaction between the ventral and dorsal streams, which is also linked to embodied cognition.